2008
DOI: 10.1007/s11248-008-9218-z
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma contamination of murine embryonic stem cells affects cell parameters, germline transmission and chimeric progeny

Abstract: Murine embryonic stem cells (mESCs) inoculated at passage P13 with the mycoplasma species M. hominis, M. fermentans and M. orale and cultured over 20 passages showed reduced growth rate and viability (P < 0.0001) compared to control mESCs. Spectral karyotypic analysis of mycoplasma-infected mESCs showed a number of non-clonal chromosomal aberrations which increased with the duration of infection. The differentiation status of the infected mESCs was most affected at passage P13+6 where the infection was stronge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…In this study, the false negative results for enzymatic method were observed in only two cell lines i.e., PEER (NCBI C511) and SH-SY5Y (NCBI C611). In the other 28 cases, the mycoalert Ò results were concordant with the real-time PCR results (Mariotti et al 2008;Markoullis et al 2009;Volokhov et al 2011;Molla Kazemiha et al 2014).…”
Section: Discussionsupporting
confidence: 59%
“…In this study, the false negative results for enzymatic method were observed in only two cell lines i.e., PEER (NCBI C511) and SH-SY5Y (NCBI C611). In the other 28 cases, the mycoalert Ò results were concordant with the real-time PCR results (Mariotti et al 2008;Markoullis et al 2009;Volokhov et al 2011;Molla Kazemiha et al 2014).…”
Section: Discussionsupporting
confidence: 59%
“…Because of incomplete respiration pathway in mycoplasma and the absence of tricarboxylic cycle and cytochrome, the ATP production that depends on oxidative phosphorylation (except malate dehydrogenase avtivity) is stopped. Therefore, the fermentative arginine and carbohydrate pathways are considered as ATP production survival systems in mollicultes (except in ureaplasmas for which ATP production depends on urea hydrolysis) (Markoullis et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…From more than 200 mycoplasma species, 20 have been isolated from cell cultures (Uphoff and Drexler 2013). Eight species including M. arginini, M. fermentans, M. hominis, M. orale, M. hyorhinis, M. salivarium, M. pirum and A. laidlawii are responsible for more than 95 % of cell culture contaminations (Harlin and Gajewski 2008;Markoullis et al 2009;Timenetsky et al 2006). The main sources of mycoplasma contamination in cell cultures are laboratory staff, serum, culture media, materials, reagents, instruments and previously contaminated cells.…”
Section: Introductionmentioning
confidence: 99%
“…Pathogen status of the ES cell line also affects various properties of ES cells, including their germline transmissibility. It has been demonstrated in mouse ES cells that the presence of virus, bacteria, or Mycoplasma affects germline transmissibility [24,25]. In our study, we conducted a comprehensive test for rat pathogens, such as H1 parvovirus, Kilham's rat virus, Mycoplasma spp., rat minute virus, and rat parvovirus.…”
Section: Discussionmentioning
confidence: 99%